2014
DOI: 10.1145/2601097.2601141
|View full text |Cite
|
Sign up to set email alerts
|

Pinlight displays

Abstract: Figure 1: A) A sparse array of point light sources, called pinlights, fill the eye's image plane when held defocused near the eye. B) Prototype optical see-through display consisting of pinlight arrays and spatial light modulators (LCDs). The spatial light modulators code the defocused pinlights to form an image on the retina. C) A photograph taken through our prototype display using a camera that approximates the human eye. D) A comparison of the field of view of our prototype display (110 • ) to state-of-the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(13 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…This includes significantly broader fields of view (e.g. [132]), and mobile and miniaturized depth based sensors (e.g. Google Tango, Occipital, Microsoft HoloLens) especially suitable for portable and wearable applications.…”
Section: Future Wearables and Smart Environments: Forthcoming Developmentioning
confidence: 99%
“…This includes significantly broader fields of view (e.g. [132]), and mobile and miniaturized depth based sensors (e.g. Google Tango, Occipital, Microsoft HoloLens) especially suitable for portable and wearable applications.…”
Section: Future Wearables and Smart Environments: Forthcoming Developmentioning
confidence: 99%
“…Computational displays combine displays, computation, optics, and knowledge of the human visual system in novel ways. The Pinlight display (Maimone et al, ) was the first example I saw that achieved a wide FOV display in a form factor resembling normal glasses. It had low image quality so it does not by itself solve the entire problem, but nonetheless the Pinlight display is a milestone, suggesting it may be feasible to achieve wide FOV in a compact form factor.…”
Section: Technical Challenges and Obstaclesmentioning
confidence: 99%
“…Several different optics architectures have been explored to implement LF-3D displays, such as super multi-view systems utilizing an array of projectors [17] or integral imaging methods using a lenslet array or pinhole array [13,19]. A computational multilayer light field display is a relatively new, emerging method of implementing LF-3D displays.…”
Section: Introductionmentioning
confidence: 99%
“…Engineering prototypes of computational LF-3D display systems have been demonstrated, and some aspects of the imaging properties such as the depth of field (DOF) have been investigated [14][15][16]19,[21][22]27]. For instance, adapted from the well-known parallax-barrier autostereoscopic displays by introducing content-adaptive optimization to compute the proper attenuation values for the mask layers, Wetzstein et al demonstrated a new tensor display comprised of a stack of time-multiplexed light-attenuating layers illuminated by a directional backlight [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation